DEVELOPMENT OF HIGHLY PATHOGENIC AVIAN INFLUENZA VACCINE FOR PANDEMIC INFLUENZA PREPAREDNESS: A REVIEW - S,Si, M.Biomed, Debie Rizqoh (JURNAL KEDOKTERAN RAFLESIA, 2024)
The Highly Pathogenic Avian Influenza (HPAI) H5N1 virus caused extraordinary incidents in several countries, especially Asia, Africa, and Europe. The disease's fatality rate caused by the H5N1 virus reaches 60%. This incident raised concerns about a wider HPAI H5N1 virus pandemic if effective human-to-human transmission occurred. Therefore, the World Health Organization (WHO) calls on all countries to prepare themselves for a pandemic that may occur. One of the strategies in preparation for this pandemic is to develop a vaccine. So far, vaccines are effective in disease prevention efforts because they can work to trigger a natural immune response and induce a memory response against the pathogen in question. Several strategies are needed to develop an effective influenza vaccine in carrying out vaccine development research and in-depth understanding of (i) virology, (ii) virus life cycle, (iii) host immune response to infection, (iv) pathology, and (v) HPAI H5N1 vaccine development strategy. Until now, many HPAI H5N1 vaccines have been developed, from vaccines developed using conventional methods to alternative vaccines using more modern methods. The results of the development of the vaccine are expected to provide provisions for a possible pandemic caused by the HPAI H5N1 virus. Keywords : Influenza, virus, vaccine